Community Empowerment Through Nagari-Owned Enterprises In Tourism Development - Nahara, Fauzana Azmin; Miko, Alfan; Damsar, Damsar (LPPM Universitas PGRI Sumatera Barat, 2023)
BUMNag was very important for improve the economy of the nagari community. The important role played by BUMNag has an effect on aspects of community development both materially and non-materially. The aim of the research is to explain BUMNag's efforts in community empowerment, explain BUMNag's efforts in achieved success in manage tourist villages, and explain the management of sustainable tourism as an instrument of BUMNag in strengthened nagari autonomy and community welfare. then an analysis tool or theory is need to explain the above problems, one of which is use in this study is Jim Ife's theory regarding community empowerment carried out by BUMNag. This research uses a qualitative approach, a case study approach. Data collection was carried out in the form of in-depth interviews, observation and document collection. The informant selection technique used was purposive. The results of the study found that BUMNag community empowerment efforts took the form of increased community skills, providing capital for BUMNag, BUMNag pro-community, increased community knowledge, and involved the community in every activity. The benefits obtained through BuMNag was achieved successful management of tourist villages in the form of benefits from managing destinations can be distributed to the community, management is running well, established strong partners and support from within and from outside, the uniqueness of the attraction must be maintained for the sustainability of destinations, and contributed to sustainability culture and environment. Sustainable tourism management as an instrument for BUMNag in strengthened nagari autonomy and community welfare as an instrument for strengthened nagari autonomy and as an instrument for community welfare.